Violence in ancient Christianity : victims and perpetrators - Geljon, Albert C. (Vigiliae Christianae, Supplements, 2014)
Ancient Christianity had an ambivalent stance toward violence. Jesus had instructed his disciples to love their enemies, and in the first centuries Christians were proud of this lofty teaching and tried to apply it to their persecutors and to competing religious groups. Yet at the same time they testify to their virulent verbal criticism of Jews, heretics and pagans, who could not accept the Christian exclusiveness. After emperor Constantine had turned to Christianity, Christians acquired the opportunity to use violence toward competing groups and pagans, even though they were instructed to love them personally and Jewish-Christian relationships flourished at grass root level. General analyses and case studies demonstrate that the fashionable distinction between intolerant monotheism and tolerant polytheism must be qualified.